Prediktivno upravljanje sinkronim motorom s unutarnjim trajnim magnetima s ciljem minimiziranja elektromagnetskih gubitaka : doktorski rad - Jerčić, Tino; Žarko, Damir (Zagreb : Tino Jerčić; Fakultet elektrotehnike i računarstva, 2018)
U radu je opisan sustav upravljanja sinkronog stroja s trajnim magnetima s ciljem primjene
u elektriˇcnoj vuˇci. Zahtjev koji se postavlja na upravljaˇcki sustav elektriˇcnim
strojem u vucˇi je osigurati slijed¯enje referentne vrijednosti momenta uz minimizaciju
elektromagnetskih gubitaka. Minimizacija gubitaka sinkronog stroja s trajnim magnetima
postiže se prikladnim izborom vektora struje. Takod¯er, odabirom vektora struje
osigurano je i postizanje referentne vrijednosti momenta. Uz minimizaciju gubitaka i
slijed¯enje referentne vrijednosti momenta uz dobar dinamicˇki odziv, zadatak sustava
upravljanja je i osigurati siguran rad sustava i zadovoljenje ograniˇcenja napona i struje.
Sustav upravljanja sinkronim motorom s unutarnjim trajnim magnetima s ciljem
minimizacije gubitaka i uz osiguranje rada motora unutar ograniˇcenja predstavljen u
radu kaskadne je strukture upravljanja podijeljene na tri zasebna elementa. Prvi element
predstavlja raˇcunski uˇcinkovit postupak proraˇcuna referentnih vrijednosti struja
u d i q osi koje rezultiraju minimalnim gubicima pri zadanom momentu i brzini vrtnje
motora. Druga i tre´ca komponenta algoritma upravljanja služe za adaptaciju izlaza
iz algoritma minimizacije gubitaka kako bi se osigurao rad motora unutar ograniˇcenja.
Druga komponenta, upravitelj referenci mijenja referentne struje u svrhu izbjegavanja
zasi´cenja strujnih regulatora i nadmodulacije bez gubitka performansi upravljanja
ˇcime se smanjuju gubici pri naglim promjenama momenta karakteristiˇcnima u
vuˇci. Tre´ca komponenta izvedena je u obliku upravljanja utemeljenog na prediktivnim
modelima kojim se garantira rad motora unutar limita i minimalni gubici u podruˇcju
slabljenja polja. Predloženi algoritam upravljanja zamišljen je kao raˇcunski uˇcinkovit
dodatak postoje´cem klasiˇcnom vektorskom upravljanju sinkronim motorom s unutarnjim
trajnim magnetima u cilju poboljšanja performansi.
Polazište razvoja algoritma upravljanja je prikladan matematiˇcki model sinkronog
stroja s trajnim magnetima. Model je zapisan u obliku naponskih jednadžbi stroja i
jednadžbe momenta u dvoosnom rotiraju´cem dq sustavu. Pojednostavljeni model koji
se koristi prilikom razvoja algoritama ukljuˇcuje i model elektromagnetskih gubitaka
stroja. Gubici u namotima se u ovom modelu raˇcunaju kao omski gubici na otporu
namota pri ˇcemu se zanemaruje utjecaj potiskivanja struje u vodiˇcu ili efekt blizine.
Gubici u željezu raˇcunaju se preko nadomjesnog otpora, što rezultira pogrešnom procjenom
gubitaka pri optere´cenju. U radu je prikazano detaljno istraživanje gubitaka
u željezu izraˇcunatih simulacijama temeljenima na metodi konaˇcnih elemenata i gubitaka
dobivenih obradom mjerenja na sinkronom stroju s unutarnjim trajnim magnetima.
Prikazan je i novi empirijski model za proraˇcun gubitaka u željezu kojim je
greška u procjeni gubitaka smanjena u odnosu na klasiˇcan model gubitaka.
Predstavljeni sustav upravljanja ispitan je kroz raˇcunalne simulacije i ispitivanja na
stvarnom sustavu, i to na dva razliˇcita tipa sinkronih strojeva: na sinkronom stroju s
trajnim magnetima na površini rotora op´ce namjene i sinkronom stroju s unutarnjim
trajnim magnetima projektiranom za elektriˇcnu vuˇcu.
Kljuˇcne rijeˇci: Sinkroni motor s trajnim magnetima, slabljenje polja, minimizacija
gubitaka, upravitelj referenci, optimalno upravljanje
Permanent magnet synchronous machine (PMSM), due to its inherently high torque
density and premium efficiency, stands out as a motor of choice in a wide array of
applications and especially proves as a perfect fit in electric traction applications. In
order to fully utilize its advantages a proper control system must be employed. In
traction applications, the main objective is to ensure reaching the reference torque with
a good dynamic performance while achieving loss minimization in the steady state.
This can be achieved by a proper current control algorithm which must respect PMSM
drive voltage and current limits.
High performance control of permanent magnet synchronous machines can be achieved
using rotor-field-oriented vector control. Usually, d and q axis currents are controlled
independently using two PI controllers with additional decoupling terms. Due
to a limited voltage available from the inverter, the current controllers are prone to saturation
which leads to disturbed current dynamics, degraded torque production and
potentially the system instability. In order to overcome the problem of saturation, the
adaptation of current references in the form of a reference governor is implemented in
the control structure of a permanent magnet synchronous machine. In order to ensure
that voltage and current constraints are not violated in steady state, i.e. to ensure reachability
of the torque reference, a novel field-weakening algorithm is also introduced.
The presented algorithms are robust to parameter changes, thereby allowing the use of
incorrectly assessed motor parameters and implementation on the motor with a high
degree of saturation.
With addition of loss minimization requirement, the control strategy of a permanent
magnet synchronous machine can be divided into three segments: an algorithm
for finding the optimal current vector which minimizes the copper losses or total copper
and iron losses in a steady state, field-weakening algorithm which ensures that
voltage constraints are not violated in steady state, and a control algorithm responsible
for tracking of reference current trajectory. In this thesis, a new formulation for
minimization of copper and iron losses in interior permanent magnet motor for the
purpose of minimum loss control is presented. Motor losses are formulated based on
electromagnetic torque to total torque ratio resulting in simplified expression of minimal
loss condition which can be easily solved online.
The problem of permanent magnet synchronous motor control with the aim of minimizing
losses and ensuring machine performance within the limits is implemented
as a cascading control structure in three parts. The first part presents a computationally
efficient calculation of the reference values of d and q axis current components resulting
in minimum losses at the given torque and machine speed. The second and third components
of the control algorithm serve to adapt the output from the loss minimization
algorithm to ensure machine operation within the limits. The second component, the
reference controller, changes the reference current to avoid the saturation of current
regulators and over-modulation without loss of control performance, thus reducing
losses due to sudden changes in torque reference. The third component is implemented
as a management model based on predictive models that guarantee machine performance
within the limits and minimum losses in the field weakening regime. The
proposed control algorithm is designed as a computationally efficient addition to the
existing classical vector-controlled permanent magnet synchronous machine in order
to improve its performance.
Modern synchronous permanent magnet motors are characterized by high efficiency
and high torque density, which are the properties increasingly emphasized in a
number of applications like electric traction or aerospace applications. Such machines
fully utilize their magnetic circuit which results in saturation phenomena that cause
nonlinearities in their mathematical models. The machine model that is able to adequately
simulate current, voltage and torque waveforms is one of the key requirements
for designing the control system and also for the purpose of the machine design optimization.
In the thesis, mathematical model of a permanent magnet synchronous
machine which includes saturation effects is presented. To round up mathematical representation
of a permanent magnet synchronous machine, the proper model of losses
must be included in the machine model used either for simulation purposes or as a
cornerstone of control algorithm design. Losses of permanent magnet synchronous
machines can be devided into two groups, mechanical and electromagnetic losses, of
which control designer can affect only electromagnetic losses.
The electromagnetic losses of synchronous motors with permanent magnets can be
divided into three categories: copper losses, iron losses and permanent magnet losses.
Copper losses are implemented in the mathematical model using winding resistance,
while iron losses are implemented using equivalent resistance of iron losses. Losses
in permanent magnets are, due to its low value compared to copper and iron losses,
neglected during control algorithm design process.
Approximation of iron losses with equivalent resistance results in an error under
load and at high speeds. In order to obtain a more acurate and detailed model of iron
losses in synchronous motors with permanent magnets, an empirical model of iron
losses was developed. The presented empirical model of iron losses is compared to the
measurement results on the real machine.
The subject and focal point of the research problem is the interior permanent magnet
synchronous machine designed as the main traction motor of an electric tram. Therefore,
an emphasis is placed on the electric traction applications.
The thesis is divided into 6 chapters organized as follows:
Chapter 1, Introduction draws the attention of the reader to the subject of the research,
the permanent magnet synchronous machine, its application, advantages and
classification. In brief, the requirements for the control system of this type of machine
are presented, as well as a detailed review of the literature.
Chapter 2, Permanent magnet synchronous machine model contains derivation of mathematical
model of a permanent magnet synchronous machine in three-phase abc reference
frame and rotating dq reference frame. This chapter provides a review of models
suitable for computer simulation.
Chapter 3, Permanent magnet synchronous machine losses presents an upgrade of a mathematical
model of the machine by adding the loss model. Breakdown of losses due to
their origin on electrical and mechanical losses and a detailed description of the appropriate
loss components is presented. A simplified requirement for minimum electrical
losses is presented with a proposal for finding solution to a minimum loss problem.
Also, the chapter describes a new empirical model of permanent magnet synchronous
machine core losses. The chapter contains two original scientific contributions:
1. Simplified model of total electromagnetic losses of interior permanent magnet
machine suitable for solving in real-time control systems
2. Empirical model for calculation of iron losses in permanent magnet synchronous
machine
Chapter 4, Permanent magnet synchronous machine control system describes the classical
vector control structure of a permanent magnet synchronous machine based on
the field oriented control. The chapter also describes a control algorithm that provides
machine operation within the limits in two components. The first component, the
reference governor, is an add-on that can be easily embedded into existing classical
control structures and whose task is to customize input references to existing current
controllers to avoid their saturation and avoid over-modulation without loss of control
performance. The second component, the field weakening algorithm, is derived in the
form of control based on predictive models to guarantee machine performance within
the voltage and current limits with minimum losses in the field weakening regime.
These two components represent two distinct original scientific contributions:
1. Algorithm for dynamic modification of permanent magnet synchronous machine
current reference values, which ensures machine performance while satisfying
the voltage and current limitations
2. Computationally efficient permanent magnet synchronous machine model predictive
control which assures field weakening operation while meeting the voltage
and current limitations
Chapter 5, Experimental results contains a detailed description of the methods and
equipment used in the experimental tests. The results of testing and the functionality
of the proposed control algorithm are given for two different permanent magnet synchronous
machines: an interior permanent magnet synchronous machine and a surface
mounted permanent magnet synchronous machine. The results of loss measurement
and comparison with the empirical model of losses from Chapter 3 are also included
in this chapter.
Chapter 6, Conclusion gives an overview of the presented dissertation and sums up
the results of the research.
Keywords: Permanent magnet synchronous machine, Field oriented control, Optimization,
PI control, Nonlinear control systems, Field weakening, Reference governor
Bibliografija str. 141-149.